The Intersection of Personality Traits and Social Media Use: Implications for Adolescent Happiness - Tabitha Grace Christiaan; Heru Astikasari Setya Murti (Universitas PGRI Yogyakarta, 2026)
This study investigates the influence of Big Five personality traits and social media use on the happiness of adolescent users of platform X (Twitter). Platform X was chosen due to its high level of toxicity compared to other platforms (Norton, 2022), making it especially relevant for exploring digital well-being in adolescents. A total of 282 adolescents aged 12 to 21 years were selected using purposive sampling. Instruments used included the IPIP-BFM-25 Indonesia, the Social Networking Time Use Scale (SONTUS), and the Oxford Happiness Questionnaire (OHQ). Data were analysed using multiple linear regression to examine both joint and partial effects. The results indicated that the independent variables jointly have a significant impact on happiness. Partially, Neuroticism and social media use had adverse effects, while Extraversion, Agreeableness, and Openness had positive effects. Conscientiousness showed no significant influence. These findings suggest the need for school-based interventions to strengthen adolescents’ emotional regulation and digital literacy. Keywords: personality, social media use, happiness, adolescents